2006
DOI: 10.1055/s-2006-924079
|View full text |Cite
|
Sign up to set email alerts
|

The Leu7Pro Polymorphism of Neuropeptide Y is Associated with Younger Age of Onset of Type 2 Diabetes Mellitus and Increased Risk for Nephropathy in Subjects with Diabetic Retinopathy

Abstract: Several studies have shown genetic predisposition for diabetic complications. The leucine7 to proline7 (Leu7Pro) polymorphism of preproNPY has been shown to be a risk factor for diabetic retinopathy in type 1 diabetes. In the current study we examined the contribution of this polymorphism on the progression of retinopathy in Caucasian type 1 and type 2 diabetes patients. Patients with type 2 diabetes and the Leu7Pro polymorphism developed retinopathy at younger age because of markedly earlier disease onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…The L7P polymorphism, first described by our group, is associated with earlier onset of type 2 diabetes in obese carriers of L7P (35) and with other traits of the metabolic syndrome (36 -39). Clinical studies have also shown that L7P carriers have altered insulin and ghrelin responses (40,41).…”
Section: Discussionmentioning
confidence: 95%
“…The L7P polymorphism, first described by our group, is associated with earlier onset of type 2 diabetes in obese carriers of L7P (35) and with other traits of the metabolic syndrome (36 -39). Clinical studies have also shown that L7P carriers have altered insulin and ghrelin responses (40,41).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies to date have looked at the molecular determinants of age of type 2 diabetes onset [19][20][21][22][23][24][25][26][27]; however none have explored mtDNA content as a candidate factor. Our study suggests that an earlier age of type 2 diabetes onset is associated with a lower PBMC mtDNA content and that this relationship occurs primarily in patients without diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Leucine 7 to Proline 7 polymorphism in the NPY gene (substitution of leucine for proline in human prepro-NPY) was linked to an increased predisposition to develop diabetic retinopathy in Type 2 diabetic patients (Jaakkola et al, 2006;Koulu et al, 2004;Niskanen et al, 2000). However, this was not considered a risk factor for exudative age related macular degeneration (Kaarniranta et al, 2007).…”
Section: Npy System In Retinal Vascular Cells: Pericytes and Endothelmentioning
confidence: 99%